Unicorn exhibit - Falk, Jon (Philadelphia Evening Bulletin, 1978)
"Bobbi Seliner, designer and coordinator of unicorn exhibit at Academy of Natural Sciences, measures narwhal (not unicorn) tusks." With clipping